Libraries & information centres balanced scorecard & key performance indicators (KPIs) - Azahar, Mohd Noor (Penang Public Library Corporation Malaysia, 2010)
International Conference On Marketing, Promoting & KPI for Library & Information Centre Services 2010 organized by Penang Public Library Corporation Malaysia and co-organized by Goethe-Institute Malaysia, 25th - 26th October 2010 at Penang Public Library Corporation Malaysia, Penang, Malaysia.